If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 7 = 10 Reorder the terms: 7 + 3y = 10 Solving 7 + 3y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3y = 10 + -7 Combine like terms: 7 + -7 = 0 0 + 3y = 10 + -7 3y = 10 + -7 Combine like terms: 10 + -7 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 3s+3=2s+10 | | 40=8-17k | | -4(-2x+3)+(-6x+8)= | | 5(x+2)+6= | | 307+x=451 | | 0.9*4= | | -7x-18=-158 | | 0.9+4= | | W-1+19=7 | | (8+2x)(24+2x)=228 | | 1/3+1/3+1/3*4= | | (X-1)(x+3)=5(x-1) | | 8y=40x+4 | | 1/3+1/3+1/3= | | 3y-6+7y+4y= | | 5k-6= | | 8*x^2-72x-288=0 | | d^2-4d-96= | | x/(10-x)=0.19 | | -.75x+.25=.5x-.75 | | 18+7x-12+5= | | 13n=-104 | | 97=7x-6(x-18) | | -5x^2=20 | | 92=-4(1-4r) | | ln(X+5)-2=ln(7-x)+3 | | x^3-7x^2-53x+315=0 | | 3x+2-= | | -2y-18=5y+3 | | 7r-3r+5=1+10-4r | | (x^2-9)(x+2)=0 | | 7x-12+2x+9+2x+9=180 |